Ratio Legis of the Deed of Sale and Purchase Agreement as an Object of Land and Building Acquisition Duty - Isma Faradila; Istislam Istislam; Arini Jauharoh (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research attempts to unravel the various dynamics governing BPHTB. This research focuses on examining two issues, namely (1) the ratio legis of PPJB regulation as the object of BPHTB and the implications of PPJB as the object of BPHTB after the issuance of Law 1/22 which amended the previous BPHTB Law as a whole. In this paper, it is found that there are several reasons that make PPJB as the object of BPHTB, namely: (1) based on the social function of land based on the agrarian law regime, so that every acquisition of land rights is taxed which is used as a net regional income; (2) the imposition of BPHTB on PPJB as an increase in regional income; (3) from the nature of PPJB as a binding transaction and as a marker of a legal event which is then followed by the making of AJB as the basis for the acquisition of land rights. Second, the implications of BPHTB for the changes in the original regulation in the PDRD Law which was later revoked by the 2022 HKPD Law, have made several changes that affect the legal certainty of taxpayers in paying BPHTB. There is an antinomy in regulating the time payable and payment of BPHTB to the local government.  The time payable arrangement as the basis for payment is made after the signing of the sale and purchase deed. However, the payment arrangement states otherwise, namely at the time the sale and purchase deed is signed. However, on the other hand, the regulation also requires the notary to request proof of payment before the signature of the sale and purchase deed. The difference in provisions on the time payable and the deadline for payment affects the legal certainty of the sale and purchase process, and is not in accordance with the meaning of BPHTB as a duty paid after the acquisition of land rights. In addition to the implications that arise for taxpayers, the above arrangements also affect the legal certainty of notaries / PPATs who carry out their duties which are overshadowed by sanctions if they sign the deed before BPHTB is paid in full.  The research method used in this writing is normative juridical research method, using three types of approaches, namely historical approach, legislative approach and conceptual approach. The urgency of implementing tax collection on deeds of acquisition of land rights known as BPHTB is to emphasise the social function of land through tax collection carried out by the government. PHTB on PPJB is one of the sources of local revenue used to organise local government and third, namely from the nature of PPJB which is an agreement that binds both parties to the certainty of the transaction being carried out, as the initial act of the legal event of sale and purchase in question.